2007
DOI: 10.1590/s0101-20612007000300009
|View full text |Cite
|
Sign up to set email alerts
|

Caracterização de amidos de mandioca nativos e modificados e utilização em produtos panificados

Abstract: ResumoO amido de mandioca é utilizado como ingrediente principal na fabricação de biscoitos e pão de queijo. O polvilho azedo é um produto artesanal, sem padrão de qualidade estabelecido, com problemas de higiene em seu processamento e de oferta. O trabalho teve como objetivo caracterizar amidos de mandioca nativos e modificados e testá-los na elaboração de pão de queijo e biscoito de polvilho. As principais características que diferem o polvilho azedo do amido de mandioca nativo, também denominado polvilho do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0
8

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(26 citation statements)
references
References 10 publications
2
14
0
8
Order By: Relevance
“…These modifi cations of the starches arose as a result of the limitations of pastes and gels obtained from native starches for application in the food industry (SILVA et al, 2006 Have developed so some work in order to verify the effect of these modifi ed starches for breadmaking food. APLEVICZ & DEMIATE (2007) study for characterization of native and modifi ed manioc starch observed that the modifi ed starch with hydrogen peroxide showed a high degree of expansion and higher percentage of transmittance, thus forming folders clearer starch, these desirable characteristics for preparation of cheese bread and biscuit recipes. SILVA et al (2006) studied the physicochemical characteristics of modifi ed starches used in food modifi ed starches had reported that technological properties of interest for some applications in the food industry such as the strength of your folders to cycles of freezing and thawing , with its interesting job frozen cheese loaves , since the release of water affects the quality of the fi nal product and high expansion when used in the production of biscuits observed that the modifi ed starch with hydrogen peroxide showed a high degree of expansion and higher percentage of transmittance, thus forming folders clearer starch, these desirable characteristics for preparation of cheese bread and biscuit.…”
Section: Introductionmentioning
confidence: 99%
“…These modifi cations of the starches arose as a result of the limitations of pastes and gels obtained from native starches for application in the food industry (SILVA et al, 2006 Have developed so some work in order to verify the effect of these modifi ed starches for breadmaking food. APLEVICZ & DEMIATE (2007) study for characterization of native and modifi ed manioc starch observed that the modifi ed starch with hydrogen peroxide showed a high degree of expansion and higher percentage of transmittance, thus forming folders clearer starch, these desirable characteristics for preparation of cheese bread and biscuit recipes. SILVA et al (2006) studied the physicochemical characteristics of modifi ed starches used in food modifi ed starches had reported that technological properties of interest for some applications in the food industry such as the strength of your folders to cycles of freezing and thawing , with its interesting job frozen cheese loaves , since the release of water affects the quality of the fi nal product and high expansion when used in the production of biscuits observed that the modifi ed starch with hydrogen peroxide showed a high degree of expansion and higher percentage of transmittance, thus forming folders clearer starch, these desirable characteristics for preparation of cheese bread and biscuit.…”
Section: Introductionmentioning
confidence: 99%
“…The specific volume and height of GF cheese bread are indicators of the baking expansion capacity for the starch and the additives used in this baking product. The specific volume of the samples was higher than those reported elsewhere (Lemos et al ., ; Rodriguez‐Sandoval et al ., ; Anjos et al ., ; López‐Tenorio et al ., ), but it was lower compared to GF cheese bread that uses Expandex ® starch (Aplevicz & Demiate, ). The height values were similar to those reported by other authors (Rodriguez‐Sandoval et al ., ; Anjos et al ., ; López‐Tenorio et al ., ).…”
Section: Resultsmentioning
confidence: 97%
“…This multipurpose polymer is also used in a large number of processes, especially in the cosmetics, pulp and paper, chemical, textile and pharmaceutical industries. A more recent application has been in the development of biomaterials (APLEVICZ & DEMIATE, 2007;ARAUJO-FARRO et al, 2010). Research institutions and industries, therefore, are becoming more interested in identifying native starches with specific characteristics, as well as improving the extraction process towards greater purity and yield (LEONEL, 2007).…”
Section: Introductionmentioning
confidence: 99%